1981
DOI: 10.1002/jsscb.1981.380160405
|View full text |Cite
|
Sign up to set email alerts
|

The structure of fibronectin and its role in cellular adhesion

Abstract: Fibronectin is a large, adhesive glycoprotein which is found in a number of locations, most notably on cell surfaces, in extracellular matrixes, and in blood. Fibronectin had been detected in all vertebrates tested and in many invertebrates. Its presence in sponges is significant because this suggests that fibronectin may have appeared very early in evolution, possibly with the most primitive multicellular organisms. Cellular and plasma fibronectins have many striking similarities. However, the locations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(22 citation statements)
references
References 97 publications
0
21
0
1
Order By: Relevance
“…A possible explanation for the differences between the results of these reports and the present study can be linked to the differences in the extracellular matrix binding the cells. In the osteoblasts, fibronectin is primarily responsible for the adhesion between the substrate and cells 19,20) . In contrast, laminin is primarily related to the adhesion between the substrate and keratinocytes in addition to the fibronectin 21) .…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the differences between the results of these reports and the present study can be linked to the differences in the extracellular matrix binding the cells. In the osteoblasts, fibronectin is primarily responsible for the adhesion between the substrate and cells 19,20) . In contrast, laminin is primarily related to the adhesion between the substrate and keratinocytes in addition to the fibronectin 21) .…”
Section: Discussionmentioning
confidence: 99%
“…However, it was reported that fibronectin has DNAbinding domains and their structures have been identified. 20,21) Therefore, the binding of fibronectin to pDNA is likely to be an important mechanism for the interaction between lipoplex and fibronectin. Fetuin is known as an α2-HS glycoprotein and shows opsonin activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that precoating titanium with fi bronectin enhanced the adhesion of cells to the titanium (1,19). The biological function of fi bronectin was evaluated by counting initially attached cells (7,9).…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin is known to play an important role in governing the interactions of biomaterials with their surrounding matrices (1,19). It was also reported that precoating materials with fi bronectin enhanced cell adhesion to the substrate (4,5).…”
mentioning
confidence: 99%